Cracking mechanisms in large size ingots of high nickel content low alloyed steel. (October 2016) - Bitterlin, Matthieu; Loucif, Abdelhalim; Charbonnier, Nicolas; Jahazi, Mohammad; Lapierre-Boire, Louis-Philippe; Morin, Jean-Benoît
Abstract: This study is focused on determining the possible root causes for cracking after open die forging of large size ingots made of high nickel medium carbon low alloy steels. Optical and scanning electron microscopies as well as Energy Dispersion Spectroscopy (EDS) were used to examine the microstructure of the samples taken out of a cracked forged ingot. The large size of the samples permitted to investigate microstructure at different locations at the surface and in depth. Chemical analysis revealed chromium and oxygen enrichment at the grain boundaries. Grain size measurement indicated clear differences between "clean" surface zones and cracked ones, and between surface and in depth regions. The analyses indicated that fracture phenomena may be due to abnormal grain size which promotes oxide penetration into grain boundaries, resulting in their embrittlement and cracking upon cooling. Highlights: Fracture analysis of large size forged ingots made of high nickel medium carbon low alloy steel Proposed possible root causes for crack initiation and propagation Role of second phase particles in cracking of near surface regions or internal regions are identified and documented A methodology is proposed to avoid future failure during forging.